COMPARING THE EFFECTS OF DIFFERENTIATED INSTRUCTION USING STUDENT WORKSHEETS VS. QUIZIZZ ON EFL LEARNERS' VOCABULARY ACQUISITION AND LANGUAGE USAGE - Maruanaya, Hendrik; Brahmasakha, Boonma (Pattimura University, 2024)
The objective of this study was to assess the effectiveness of differentiated learning through the integration of Quizizz, compared to the use of student worksheets, on vocabulary acquisition and language usage. This study utilized a quantitative, quasi-experimental research design to compare the effect of these two instructional approaches on EFL learners' learning outcomes and perceptions. The participants were 58 Grade 8 Junior High School students, divided into a Quizizz group (n=29) and a worksheet group (n=29). The Quizizz group received differentiated instruction using the interactive Quizizz platform, while the worksheet group used traditional student worksheets. Pre-test analysis revealed no significant differences between the groups. After the one-month intervention, post-test results showed statistically significant improvements in learning outcomes for both groups. However, the Quizizz group outperformed the worksheet group on vocabulary mastery and application (t=4.71, p<0.01), with higher average scores (M=85.05) compared to the worksheet group (M=81.26). The Quizizz group also exhibited more positive attitudes towards English language learning, demonstrating higher levels of motivation, engagement, enjoyment, and interest (F=1.196, p<0.01) than the worksheet group. These findings suggest that the integration of Quizizz into differentiated learning enhances student learning outcomes and fosters a more positive attitude towards English language learning compared to traditional worksheets. The results highlight the potential benefits of incorporating technology-based approaches into differentiated instructional practices.